Enabling Technologies to Facilitate Natural Product-Based Drug Discovery from African Biodiversity - Chigorimbo-Murefu, Nyaradzo T. L.; Mugumbate, Grace; Chibale, Kelly (John Wiley & Sons, Ltd, 2022)
Africa disproportionately bears the brunt of the global disease burden. It has the highest prevalence of infectious diseases and some of them are unique to the continent, such as tsetse-transmitted trypanosomosis. Consequently, it is imperative for Africa to find therapies to such diseases. In spite of the intellectual and scientific capacity on the continent, as well as the rich natural resources it possesses, Africa is yet to supply a drug on the market. This chapter discusses some of the platforms that will enable Africa to effectively participate in the discovery of new drug entities. The application of these technologies to natural products is explored in detail and their relevance to Africa highlighted.